The Review Of Problems, Preconditions and Economic Consequence of Intellectualization Processes in Oil and Gas Sector of Ukraine - Кісь, С. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article analyzes the main results and potential economic activities of oil and gas in Ukraine. The attention on the fact that "Naftogaz Ukraine" as a company that generates results for most of the industry does not provide the processes meet the statutory objectives - improving energy security. In this paper, using his prior work, the author proved that the results of economic activity of NVC Ukraine is a consequence of Processes of intellectualization. In particular, the example of "Naftogaz Ukraine" demonstrated that the increase in the share of higher intelligence in the management of the company has allowed a positive economic effect. Adapted to the conditions of NGK Ukraine dependence Gisela E. allowed to draw a conclusion about the need to enhance the intellectualization of lower levelsof managementl and executive staff of oil and gas industry. The estimated values of the transformation of resources into results for NGK Ukraine and demonstration of its dynamics, on the one hand confirm the assumption of economic efficiency intellectualization process, on the other - indicate the need to enhance economic activities in all of the industry.